The implication of profit efficiency on credit risk: Evidence from US commercial banks - Yang, Yuxi (2019)
This study measures bank profit efficiency and studies its relationship with credit risk of 300 commercial banks in the United States from 2014 to 2018. The estimation of profit efficiency adopts Stochastic Frontier Approach (SFA) and System Generalized Method of Moments (SGMM) is used to investigate the determinants of credit risk. The result represents a mean profit efficiency score of 72.14% from 2014-2018. The findings indicate that bank profit efficiency is one of the significant determinants of credit risk and would negatively influence credit risk. Other determinants of credit risk include GDP growth rate and Capital ratio.